Aleksandr Askol'dov. Sud'ba komissara - Balayan, Valery (Russia : Balayan, Valery, 2006)
Movie director Alexander Askoldov made only one famous movie, The Commissar. The film was too unsettlling for Soviet censorship and was therefore banned for twenty years while the director was prosecuted by the Soviet authorities and erased from the face of Russian culture.